GREEN CHEMISTRY LEARNING TRANSFORMATION: YOUTUBE INTEGRATED INTERACTIVE VIDEO TO IMPROVE CRITICAL THINKING SKILLS - Sumanik, Novike Bela; Arismunandar, Arismunandar; Nurhikmah, Nurhikmah; Indrawati, Nenny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
The use of technology as a learning medium is a necessity that needs to be fulfilled in the learning process. Technology provides a more pleasant and interesting learning atmosphere, one of which is learning media in the form of interactive learning videos. The purpose of the study was to produce a product in the form of an interactive learning video of green chemistry integrated with YouTube to improve students' critical thinking skills. The research instrument was a validation sheet, Likert scale questionnaire, interview guidelines, and pretest and posttest questions on critical thinking skills. The learning video has been validated by material experts with an average of 90% and media experts with an average of 88% in the very valid category. Furthermore, it was tested in small groups with an average of 89% and field trials with an average of 90%. The effectiveness test was 77% with the effective category. The results of this research are that the learning video products developed are valid, practical, and effective in improving students' critical thinking skills. In addition, the results of the evaluation of students showed an increase in critical thinking skills after using the learning video. The use of YouTube-integrated videos allows wider access and flexibility in learning and is by the times. This research concludes that green chemistry learning videos integrated with YouTube can be an effective alternative to chemistry learning.